Avaliação e tratamento do paciente com pé diabético na prevenção de incapacidades - Andrade da Silva, Francisco Ronner (2024)
Diabetic foot (PD) is among the most frequent complications of Diabetes Mellitus (DM) and its consequences can be dramatic for an individual's life, from chronic wounds and infections to lower limb amputations. The general objective of this study was to describe how the assessment and treatment of patients with diabetic foot occurs in the prevention of disabilities. This was a descriptive, narrative research, with an integrative literature review approach. The survey of studies was carried out using electronic databases: Virtual Health Library (VHL) and Scientific Electronic Library Online (SciELO). For this purpose, the following Health Sciences Descriptors (DECs) were used, namely: “Assessment”, “Diabetes Mellitus”, “Diabetic Foot”. The Boolean operators “AND” and “OR” were used. Initially, 47 articles were obtained, 21 Scientific Electronic Library online (SCIELO) and 26 from the Virtual Health Library (VHL), and after using the methodological criteria established for inclusion and exclusion, 10 articles were selected that best met the objectives of this study. It is concluded that in diabetic patients, the assessment of foot sensitivity through specific tests, such as monofilament and tuning fork, is essential for identifying risk factors and reducing the chances of developing diabetic foot and possible amputation, however, it is not yet It is a practice incorporated by all healthcare professionals. Furthermore, guidance regarding the use of inappropriate shoes, ineffective hydration, skin changes and signs indicative of ringworm are successful strategies in preventing patient disabilities.